The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.2044-8341.2012.02070.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical psychologists’ experiences of personal significant distress

Abstract: The paper presents research relevant to UK clinical psychologists and to trainers and employers of this group. The data presented provides a useful insight into the perception of a sample of clinical psychologists regarding what it means to be a 'good psychologist' and the potential impact on their experience of personal distress and on help seeking behaviour. The findings have potential relevance for individual psychologists, trainers, and managers of this group in considering how distress might be experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, epidemiological studies suggest that there might be a general tendency of help withdrawal or avoidance among those currently experiencing clinical and subclinical levels of different forms of distress, including suicidal thoughts (Wilson, Bushnell, & Caputi, 2011). Without deliberate attention to helper self-care, services also can foster a culture in which the helper views their health as a reflection of their competence (Charlemagne-Odle, Harmon, & Maltby, 2014; Siebert & Siebert, 2007; Wallace & Lemaire, 2009). Helping professionals report that they are unlikely to seek help for elevated personal symptoms of distress, especially from another professional (Daronkamas, Burton, & Cushway, 1994; Deutsch, 1985; Guy, 2000; Guy et al, 1989).…”
Section: Functional Impairment and Psychological Distressmentioning
confidence: 99%
“…However, epidemiological studies suggest that there might be a general tendency of help withdrawal or avoidance among those currently experiencing clinical and subclinical levels of different forms of distress, including suicidal thoughts (Wilson, Bushnell, & Caputi, 2011). Without deliberate attention to helper self-care, services also can foster a culture in which the helper views their health as a reflection of their competence (Charlemagne-Odle, Harmon, & Maltby, 2014; Siebert & Siebert, 2007; Wallace & Lemaire, 2009). Helping professionals report that they are unlikely to seek help for elevated personal symptoms of distress, especially from another professional (Daronkamas, Burton, & Cushway, 1994; Deutsch, 1985; Guy, 2000; Guy et al, 1989).…”
Section: Functional Impairment and Psychological Distressmentioning
confidence: 99%
“…Studies using more traditional epistemologies have reported that professionals with service user experience encounter dilemmas (Berry, Hayward, & Chandler, 2011;Cain, 2000;Charlemagne-Odle, Harmon, & Maltby, 2014;Gilroy, Carroll, & Murra, 2001;Stanley, Manthrope, & White, 2007;van Erp, Hendriksen-Favier, & Boer, 2010). These include issues regarding self-disclosure, experiencing stigma, prejudice and discrimination, being accused of overidentification and boundary violation, having reduced energy, confidence and emotional presence, and a discrepancy between their personal identity and their professional role.…”
Section: Introductionmentioning
confidence: 99%
“…Newly qualified clinical psychologists should be given a gradual induction to post‐qualification work and allowed their first post‐qualification year to ‘bed in’, consolidate skills and improve their confidence before being asked to take on additional responsibilities and roles. Employers should also be mindful that stress and mental health problems are not limited to trainee clinical psychologists but are prevalent in qualified staff also (Charlemagne‐Odle, Harmon & Maltby, ; Pakenham & Stafford‐Brown, ). Promotion of, and commitment to, career long personal development and self‐care should be a concern of the whole profession.…”
Section: Discussionmentioning
confidence: 99%